Hospital Antibiotic Consumption before and during the COVID-19 Pandemic in Hungary - Roxána Ruzsa; Ria Benkő; Helga Hambalek; Erika Papfalvi; Dezső Csupor; Róbert Nacsa; Márta Csatordai; Gyöngyvér Soós; Edit Hajdú; Mária Matuz (MDPI AG, 2024)
The aim of this study was to assess antibiotic use in the Hungarian hospital care sector during and before the pandemic. Aggregated systemic antibiotic (ATC: J01) utilisation data were obtained for the 2010-2021 period. Classifications and calculations were performed according to the WHO ATC/DDD index and expressed as DDD per 1000 inhabitants and per day (DID), DDD per 100 patient-days (DHPD) and DDD/discharge. A linear regression (trend analysis) was performed for the pre-COVID years (2010-2019) and a prediction interval was set up to assess whether the pandemic years' observed utilisation fit in. Antibiotic utilisation was constant in DID before and during the pandemic (2019: 1.16; 2020: 1.21), while we observed a substantial increase in antibiotic use when expressed in DDD per 100 patient-days (2019: 23.3, 2020: 32.2) or DDD/discharge (2019: 1.83, 2020: 2.45). The observed utilisation level of penicillin combinations; first-, third- and fourth-generation cephalosporins; carbapenems; glycopeptides; nitroimidazoles and macrolides exceeded the predicted utilisation values in both pandemic years. Before the pandemic, co-amoxiclav headed the top list of antibiotic use, while during the pandemic, ceftriaxone became the most widely used antibiotic. Azithromycin moved up substantially on the top list of antibiotic use, with a 397% increase (2019: 0.45; 2020: 2.24 DHPD) in use. In summary, the pandemic had a major impact on the scale and pattern of hospital antibiotic use in Hungary.